2018
DOI: 10.1371/journal.pone.0195536
|View full text |Cite
|
Sign up to set email alerts
|

Heparin free dialysis in critically sick children using sustained low efficiency dialysis (SLEDD-f): A new hybrid therapy for dialysis in developing world

Abstract: BackgroundIn critically sick adults, sustained low efficiency dialysis [SLED] appears to be better tolerated hemodynamically and outcomes seem to be comparable to CRRT. However, there is paucity of data in critically sick children. In children, two recent studies from Taiwan (n = 11) and India (n = 68) showed benefits of SLED in critically sick children.Aims and objectivesThe objective of the study was to look at the feasibility and tolerability of sustained low efficiency daily dialysis-filtration [SLEDD-f] i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 33 publications
1
23
2
Order By: Relevance
“…Of these patients, the percentage of fluid overload was lower among those who survived (5.8 ± 3.6 (6.8%) compared against those who did not survive (8.5 ± 4.5 (11.3%)). In the other study by the same group, it was seen that fluid overload was higher among those who survived compared to those who did not (mean fluid overload = 8.11 ± 7.39, among survivors: 8.83 ± 8.34, and among nonsurvivors: 6.81 ± 5.1) …”
Section: Methodsmentioning
confidence: 73%
See 4 more Smart Citations
“…Of these patients, the percentage of fluid overload was lower among those who survived (5.8 ± 3.6 (6.8%) compared against those who did not survive (8.5 ± 4.5 (11.3%)). In the other study by the same group, it was seen that fluid overload was higher among those who survived compared to those who did not (mean fluid overload = 8.11 ± 7.39, among survivors: 8.83 ± 8.34, and among nonsurvivors: 6.81 ± 5.1) …”
Section: Methodsmentioning
confidence: 73%
“…Lee et al found that children were on an average of 1.1 ± 1.4 inotropes before PIRRT initiation to an average of three inotropes in those who did not survive; the difference in survival was significantly higher . In the studies from India, it was seen that the number of inotropes in children who underwent PIRRT was 1.08 ± 1.06, and the difference in number of inotropes among those who survived vs. nonsurvivors was not significant (1.01 ± 0.98 vs. 1.32 ± 1.10) . In the other cohort from the same author, it was noted that the children were on an average of 1.1 ± 1.2 inotropes at PIRRT initiation with no difference between survivors and nonsurvivors …”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations